THE CORRELATION BETWEEN INTERNAL FACTORS AND THE ENGLISH ACHIEVEMENT OF THE SECOND SEMESTER STUDENTS OF BUSINESS ADMINISTRATION MAJOR OF THE STATE POLYTECHNIC OF SRIWIJAYA - Sri Gustiani (HOLISTICS, 2009)
The present student attempts to decsribe the correlation between students’ internal factors, i.e.: interest in English and English learning habit and their English academic achievement. The questionnaire and documents (students’ record) were using in collecting the data. Then, the data were analyzed by means of two statistical  analyses, namely Correlation Coefficient and Regression Analysis. The findings indicate that there was statistically significant correlation between students’ interest and their English learning habit, and their English achievement.